2017
DOI: 10.1093/ilar/ilw035
|View full text |Cite
|
Sign up to set email alerts
|

The Governance of Animal Care and Use for Scientific Purposes in Africa and the Middle East

Abstract: Animals are commonly used for scientific purposes in Africa and the Middle East. However, this field is often inadequately regulated, with many countries lacking national legislation, policies, or guidelines for the care and use of animals used for research, testing, or education. This results in an essentially uncontrolled system where scientific quality and animal wellbeing cannot robustly be guaranteed, which may hinder acceptance (i.e., publication) of results by the scientific community and limit public c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…This showed that a median lethal dose of 50% (LD 50 ) is larger than 2000mg/kg, which attests that plant products are frequently considered to be safe and have fewer adverse effects than synthetic ones. 37,38 However, species variations would limit such a clear-cut extrapolation of the findings of this study to humans. On subacute toxicity study of mice, there was a discount in mean weight of liver and kidneys.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This showed that a median lethal dose of 50% (LD 50 ) is larger than 2000mg/kg, which attests that plant products are frequently considered to be safe and have fewer adverse effects than synthetic ones. 37,38 However, species variations would limit such a clear-cut extrapolation of the findings of this study to humans. On subacute toxicity study of mice, there was a discount in mean weight of liver and kidneys.…”
Section: Discussionmentioning
confidence: 95%
“…The care and handling of mice were per international guidelines for the use and maintenance of experimental animals. 37,38 Chloroquine-sensitive malaria, P. berghei was obtained from EPHI in the traditional medicine research department Addis Ababa and transported by infecting the donor mice and maintained the parasite up to the actual procedure of the study.…”
Section: Animals and Parasitementioning
confidence: 99%
See 1 more Smart Citation
“…Before the experiment, they were acclimatized to the test environment for one week. The care and handling of mice were according 6 to international guidelines for the use and maintenance of experimental animals [32,33] . Chloroquine-sensitive malaria, P. berghei was obtained from EPHI in the traditional medicine research department Addis Ababa and transported by infecting the donor mice and maintained the parasite up to the main procedure of the study.…”
Section: Animals and Parasitementioning
confidence: 99%
“…The animals were handled according to the governance of animal care and use for scientific purposes in Africa and the Middle East [33] . And the ethical clearance was requested and obtained from the Department of Pharmacology, School of Pharmacy, University of Gondar for the use of animals for experiment with Ref.…”
Section: Ethical Approvalmentioning
confidence: 99%